Iatrogenic Delayed Pneumothorax After Transbronchial Biopsy - Kartikeya Rajdev MBBS; Dustin N. Herring MD; Shubham Lahan MD; Kyle Wilson MD; Peter J. Murphy MD (SAGE Publishing, 2020)
Transbronchial biopsy (TBB) is one of the commonly performed procedures by pulmonologists in everyday practice. Although the procedure has a very low-risk profile, complications often develop in certain patients. Pneumothorax is one such complication pertaining to TBB. As only a small percent of procedures get complicated by pneumothorax, handful of cases have been reported with its delayed occurrence in the past 5 decades. The purpose of our report is to highlight another uncommon yet interesting case of delayed iatrogenic pneumothorax in an immunocompromised patient after TBB. Although the chain of events behind the pathophysiology of delayed pneumothorax largely remain a mystery, its development has been linked to altered immune mechanics as they are frequently recognized in immunocompromised patients.